The Impact of Product Quality, Product Design, and Lifestyle on iPhone Purchasing Decisions - Ibnu Syaiful Amrin; Ni Luh Wayan Sayang Telagawathi; Komang Krisna Heryanda (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research aims to analyze the role of lifestyle in mediating product quality and product design on iPhone purchasing decisions in Denpasar City. Using a quantitative approach that is predetermined, statistical data analysis and statistical data interpretation. The subjects in this study were all users of iPhone products in Denpasar City. For the object of this research are product quality (X1) and product design (X2) as the independent variable, purchasing decisions (Y) as the dependent variable, and lifestyle (M) as mediation. Sample selection using non probability sampling method on iPhone users in Denpasar City. Collecting data by distributing questionnaires to 100 respondents. The analysis technique uses structural equation model (SEM) analysis based on Partial Least Square (PLS). The results of this research indicated that: (1) product quality has a positive and significant influence on lifestyle (2) product design has a positive and significant influence on lifestyle (3) product quality has a positive and significant influence on purchasing decisions (4) product design has a positive and significant influence on purchasing decisions (5) lifestyle has a positive and significant influence on purchasing decisions. In the indirect effect, it shows that (6) product quality has an influence on purchasing decisions mediated by lifestyle (7) product design influences purchasing decisions mediated by lifestyle. Practically, this research provides the implementation of company strategies to consider product quality, product design, and understand consumer lifestyles because they are factors that determine purchasing decisions, especially on iPhone products in Denpasar City.